Pulsed streamer discharge chamber to reduce nitrogen oxides from diesel engine exhaust - Roslan, Nurul Ain (2014)
Major air pollution problem contributed by Nitrogen Oxides (NOx) has a noxious effect on human health and environment. Implementation of stringent regulation of NOx emission has greatly increased interest in the development of new effective pollution control technology. Non-Thermal Plasma (NTP) utilizing electrical discharge has been recognized as a promising technology for the removal of pollutant gases from diesel engine exhaust. In this research, cascaded pulsed streamer discharge plasma reactor was designed to investigate the removal of NOx from diesel engine exhaust. A simulation study consists of flow analysis of cascaded pulsed streamer discharge plasma reactor was conducted using Commercial Computational Fluid Dynamics (CFD) to evaluate the performance of the discharge plasma chamber on the removal of NOx from diesel engine exhaust together with engine performance. Several parameters including gap spacing, chamber length and number of stages were varied to investigate their effects on system performance. The results from simulation study show that the cascaded pulsed streamer discharge plasma reactor with three stages of treatment process provides more effective performance on the removal of NOx pollutant from diesel engine exhaust without affecting engine performance. This is in line with the initial assumption that three stages cascaded chamber will effectively remove the NOx from diesel engine exhaust. A mathematical modelling by using dimensional analysis has been developed that is appropriate in investigating the relation of the electrical and physical parameters on the removal of NOx concentration from diesel engine exhaust. To verify the viability of the analysis, results obtained from the dimensional analysis were compared with the experimental results reported in previous research. These predictions calculation demonstrates a reasonable agreement with the experimental data.